Exfoliation of graphene via wet chemical routes - Parvez, Khaled; Yang, Sheng; Feng, Xinliang; Muellen, Klaus (Synthetic Metals, 2015)
Graphene is a two-dimensional material that has fascinating electrical and optical properties, and this material has provided chemists with great possibilities and challenges. Interests in graphene's exceptional physical and chemical properties and in its potential for applications have generated thousands of publications and have accelerated the pace of graphene research. Although considerable scientific progress has been achieved, the key to commercializing graphene lies in the cost-effective and scalable production of this material. Graphene can be produced using a variety of wet chemical methods, such as chemical oxidation followed by exfoliation, liquid-phase and electrochemical assisted exfoliation etc. from inexpensive and abundant sources such as graphite. This review article summarizes the recent progress toward the preparation of graphene through wet chemical routes and discusses their remaining challenges. In particular, the quality and yield of graphene sheets produced using these exfoliation protocols will be emphasized.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Exfoliation; Graphene; Wet-chemistry